2021
DOI: 10.1108/tlo-05-2021-0061
|View full text |Cite
|
Sign up to set email alerts
|

The learning organization and organizational learning in the public sector: a review and research agenda

Abstract: Purpose This study aims to propose a new research agenda for the theories of “organizational learning” and the “learning organization” in relation to the public sector. The research agenda can be used by researchers to make explicit accounts of how and where the results from their studies advance the current state-of-the-art in the intersection between public sector and organizational learning and/or the learning organization. Design/methodology/approach A combined systematic and bibliometric review methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 94 publications
0
29
0
1
Order By: Relevance
“…The foregoing is corroborated by a bibliometric study conducted by Anand and Brix (2022), who found that the learning organisation literature is dominated by the West and Europe with few from other regions. The few from Africa also have different focus.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The foregoing is corroborated by a bibliometric study conducted by Anand and Brix (2022), who found that the learning organisation literature is dominated by the West and Europe with few from other regions. The few from Africa also have different focus.…”
Section: Introductionmentioning
confidence: 71%
“…It concerns a practice where new and expansive patterns of thinking are nurtured, collective aspiration is set free and people continually learn to see the whole together. Job performance is central to learning organisations and is an important aspect of development for both employees and the organisation (Anand & Brix, 2022). Employee job performance is thought to be a set of employees' behaviours that can be observed, assessed and measured at both the individual and organisational level to determine how well a company excels (Diamantidis & Chatzoglou, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Organisational learning in the public and third sector Anand and Brix's (2021) paper provided a needed overview of key literature on the public sector, identifying key organisational learning issues and proposing a way forward. Although most of organisational learning and learning organisation concepts and studies originated in the private sector, the paper uses meta-analysis of literature to confirm the need to explore how these concepts are manifested in the public sector because of high levels of professionalism, learning through collective action and complexity of issues.…”
Section: Processes Versus Culture In Organisational Learningmentioning
confidence: 99%
“…The complexities of establishing a learning culture when the individual and organisational level views of change differ is explored in the study by Koo, Kim, and Song (2022). Anand and Brix's (2021) paper explored recent tendencies and emerging themes within the public sector exploring the intersection of organisational learning and learning organisation. Corvino, Gazzaroli, and D'Angelo (2022) explored the use of dialogic evaluation (DE) as a participatory evaluation tool to foster inter-organisational learning (IOL) across public and third sector organisations involved in sport as a developmental and social activity.…”
Section: Introductionmentioning
confidence: 99%
“…Det ene paradigme har vaeret optaget af laering som resultat, og det andet paradigme har fokuseret på laering som proces (Örtenblad, 2001). I de seneste år er et tredje paradigme inden for organisatorisk laering begyndt at spire, nemlig det integrerede paradigme (Kringelum & Brix, 2021;Anand & Brix, 2022), hvor der fokuseres på resultater og processer. En af de baerende teorier i det integrerede paradigme er Capacity Building.…”
Section: Capacity Building -Definition Og Afgraensningunclassified